(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
This paper presents and analyzes the project "Imaginary Interviews with the Past," a workshop developed based on the hypothesis that widely circulated narratives about recent history face challenges in engaging younger generations. Building on this premise, we proposed the creation of a series of podcasts in which teenagers and young adults aged 16 to 20 converse with imaginary characters who lived through Argentina’s last dictatorship and represent different roles: victims, perpetrators, or what Michael Rothberg calls "implicated subjects." by The participants created and portrayed these characters by themselves. The podcasts are the result of a workshop organized in 2021 by the University of Buenos Aires team as part of the MSCA-RISE SPEME project - Questioning Traumatic Heritage: Spaces of Memory in Europe, Argentina, Colombia.